Cryptocurrency: Advantages and Disadvantages - Subačius, Augustas; Subačienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2019)
[full article and abstract in Lithuanian; abstract in English]The main feature of the twenty-first century could be named as permanent transformation that covers all areas. Payments and money are developing and changing especially fast. Technological evolution and development have led to the emergence of new transactional techniques on the Internet, mobile phones, and credit cards. Various systems of payment / money transfer have considerably expanded payment options and possibilities. And such conditions have created opportunities for the emergence of a cryptocurrency. The purpose of the study is to investigate the cryptocurrency, its concept, advantages and disadvantages. Analysis of the scientific literature, systematization, comparison, interpretation and generalization of information research methods were used for the study. Evaluation of the reasons for the emergence of cryptocurrency let to generalise, that the process was mostly influenced by technological progress and the aspiration to find faster, cheaper and more confidential settlement tools. Cryptocurrency may be defined as digital money or property in electronical form. This currency may be characterized by properties of decentralization, uncontrollability and higher risk management. The most important advantages of using a cryptocurrency may be: the speed of settlements; cheaper financial services; additional investment opportunities. Disadvantages - unpredictable, fluctuating value; possible fraud cases; possibility to use cryptocurrency for illegal activities.
Keywords: crytocurrency; advantages of cryptocurrency; disadvantages of cryptocurrency